Existence of Solutions for a Four-Point Boundary Value Problem with a $p(t)$-Laplacian (Communications in Mathematical Research, 2021)
This paper deals with the existence of solutions to the $p(t)$-Laplacianequation with four-point boundary conditions. It is shown, by Leray-Schauder fixedpoint theorem and degree method, that under suitable conditions, solutions of theproblem exist. The interesting point is that $p(t)$ is a general function.
Keywords: $p(t)$-Laplacian; four-point boundary condition; fixed point theorem; Leray-Schauder degree method.